Does Working Capital Management Drive Firm Financial Performance? Evidence from Developing Nation - Olunuga, Adeshola Olugbenga (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
This study examines the impact of working capital management on the financial performance of Nigerian businesses. Working capital management (WCM) is an integral part of corporate finance and has a direct impact on a company's liquidity and profitability. The study utilized panel data. Companies' data were analyzed utilizing proper statistical methods. The findings show that effective working capital influence a firm’s financial performance in Nigeria. The study concluded that management should create a strong and effective working capital management strategy that ensures maximum return, increases firm share value, and maximizes shareholders’ wealth. Keywords: Working Capital Management; Firms; Financial Performance; Liquidity; Inventory Penelitian ini menguji dampak manajemen modal kerja pada kinerja keuangan bisnis Nigeria. Manajemen modal kerja (WCM) merupakan bagian integral dari keuangan perusahaan dan memiliki dampak langsung pada likuiditas dan profitabilitas perusahaan. Penelitian ini menggunakan data panel. Data perusahaan dianalisis menggunakan metode statistik yang tepat. Temuan menunjukkan bahwa modal kerja yang efektif mempengaruhi kinerja keuangan perusahaan di Nigeria. Studi menyimpulkan bahwa manajemen harus menciptakan strategi manajemen modal kerja yang kuat dan efektif yang memastikan pengembalian maksimum, meningkatkan nilai saham perusahaan, dan memaksimalkan kekayaan pemegang saham. Kata Kunci: Manajemen Modal Kerja; Perusahaan; Kinerja Keuangan; Likuiditas; Persediaan